The Ruling of Muslim Jurisprudence (Fiqh) on Utilizing the Software Program Entitled “Deep Nostalgia” for Animation of the Dead - Hammad, حمزة عبدالكريم (Dirasat: Shari'a and Law Sciences, 2022)
Objectives: The study aims to focus on the Muslim jurisprudential rule for utilizing the technique of “Deep Nostalgia”, which allows taking video shots of faces in still pictures, whereby the face appears in the fixed image moving his head, eyes, and lips in a realistic and highly precise manner without uttering words. Mostly, this software program is utilized to create video clips of deceased relatives for longing to see them. Methods: The study pursued the inductive, analytical, and critical methods, through surveying, analyzing, critiquing opinions, and then arriving at the most plausible one. Results: The study reached the conclusion that this animation technique is Islamically prohibited because it is based on contravening reality, for the claim that the dead person is smiling or frowning. The dead person has moved to the afterlife, to the unseen world. This is logical given the inordinate psychological damages stemming from utilizing this software as indicated by specialized psychiatrists. Conclusions: The study suggests conducting research on the ruling on using software to fabricate videos of the live.